LUBAC regulates ciliogenesis by promoting CP110 removal from the mother centriole - Shen, Xiao-Lin; Yuan, Jin-Feng; Qin, Xuan-He; Song, Guang-Ping; Hu, Huai-Bin; Tu, Hai-Qing; Song, Zeng-Qing; Li, Pei-Yao; Xu, Yu-Ling; Li, Sen; Jian, Xiao-Xiao; Li, Jia-Ning; et al. (The Journal of cell biology, 2022)
Primary cilia transduce diverse signals in embryonic development and adult tissues. Defective ciliogenesis results in a series of human disorders collectively known as ciliopathies. The CP110–CEP97 complex removal from the mother centriole is an early critical step for ciliogenesis, but the underlying mechanism for this step remains largely obscure. Here, we reveal that the linear ubiquitin chain assembly complex (LUBAC) plays an essential role in ciliogenesis by targeting the CP110–CEP97 complex. LUBAC specifically generates linear ubiquitin chains on CP110, which is required for CP110 removal from the mother centriole in ciliogenesis. We further identify that a pre-mRNA splicing factor, PRPF8, at the distal end of the mother centriole acts as the receptor of the linear ubiquitin chains to facilitate CP110 removal at the initial stage of ciliogenesis. Thus, our study reveals a direct mechanism of regulating CP110 removal in ciliogenesis and implicates the E3 ligase LUBAC as a potential therapy target of cilia-associated diseases, including ciliopathies and cancers.